(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this work, we consider a class of eigenvalue elliptic systems involving the fractional (p(x, .), q(x, .))-Laplacian operators. Our main tools are based on Mountain Pass Theorem and Fountain Theorem.